1997
DOI: 10.1152/ajpcell.1997.273.2.c679
|View full text |Cite
|
Sign up to set email alerts
|

Effects of P2 purinergic receptor stimulation in brown adipocytes

Abstract: Sympathetic stimulation of brown adipocytes plays a major role in body energy homeostasis by activating energy-wasting pathways. Sympathetic neuronal input initiates a variety of metabolic, developmental, and membrane responses in brown fat cells. Many of these actions are mediated by adrenergic pathways mobilized by released norepinephrine. However, since sympathetic stimulation may also release vesicular ATP, we tested brown fat cells for ATP responses. Micromolar concentrations of extracellular ATP had a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…And in some tissues (spleen and fat cells) we found expression of P2X 4 protein where it had not previously been described. Of these tissues, brown fat cells respond to extracellular ATP with a cation conductance increase (Lee and Pappone 1997), and splenic dendritic cells show an increase in [Ca] i (Nihei et al Fig. 3A, B Tissue distribution of P2X 4 subunit by Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…And in some tissues (spleen and fat cells) we found expression of P2X 4 protein where it had not previously been described. Of these tissues, brown fat cells respond to extracellular ATP with a cation conductance increase (Lee and Pappone 1997), and splenic dendritic cells show an increase in [Ca] i (Nihei et al Fig. 3A, B Tissue distribution of P2X 4 subunit by Western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that the high-fat diet induces a great increase in the weight of both white and brown adipose tissues, but leads to a reduction in sympathetic activities in brown adipose tissue (Sakaguchi et al 1989). ATP, which is thought to be co-released with noradrenaline, has been recently reported to elicit the diverse cellular effects on brown adipocytes; the elevation of cytosolic free Ca 2+ (Lee & Pappone, 1997), the increase in cell membrane capacitance (Pappone & Lee, 1996), the modulation of voltage-gated K + currents and the promotion of cell proliferation ). In the previous study, we examined the interaction between noradrenaline and ATP in brown adipocytes to clarify the cellular mechanism of sympathetic regulation on intracellular Ca 2+ levels and found that extracellular ATP evoked a transient increase in the intracellular level of Ca 2+ , while the same concentrations of ATP exerted a potent inhibitory effect on both noradrenaline-and thapsigargininduced store-operated Ca 2+ entry (Omatsu-Kanbe & Matsuura, 1999).…”
mentioning
confidence: 99%
“…In the previous study, we examined the interaction between noradrenaline and ATP in brown adipocytes to clarify the cellular mechanism of sympathetic regulation on intracellular Ca 2+ levels and found that extracellular ATP evoked a transient increase in the intracellular level of Ca 2+ , while the same concentrations of ATP exerted a potent inhibitory effect on both noradrenaline-and thapsigargininduced store-operated Ca 2+ entry (Omatsu-Kanbe & Matsuura, 1999). ATP-induced [Ca 2+ ] i elevation in rat brown adipocytes has been observed to be a strict transient form (Lee & Pappone, 1997;Omatsu-Kanbe & Matsuura, 1999). The aim of the present study was to examine the mechanism underlying the transient nature of [Ca 2+ ] i elevation during the exposure to extracellular ATP in rat brown adipocytes.…”
mentioning
confidence: 99%
“…Previously, Lee and Pappone (15) suggested that other neuronal factors besides the adrenergic system may also be involved in the sympathetic activity and proposed extracellular ATP as a candidate, because it is often co-localized in the vesicles of many sympathetic neurons and is released simultaneously with norepinephrine. The various physiological effects of P2 purinergic receptor stimulation have been well studied in brown adipocytes, including increases in cytosolic calcium levels and membrane conductance (16), enhancement of cellular metabolism (17), stimulation of exocytosis (18), and regulation of cell proliferation (19). These all indicate ATP is a factor that mediates important aspects of sympathetic stimulation in brown adipocytes.…”
mentioning
confidence: 99%